SAT0308 Tophus Resolution with Pegloticase – A Prospective Dual Energy Computed Tomography Study. (9th June 2015) - Schett, G.; Araujo, E.; Bayat, S.; Petsch, C.; Englbrecht, M.; Faustini, F.; Kleyer, A.; Hueber, A.; Cavallaro, A.; Lell, M.; Dalbeth, N.; Manger, B.; et al.
Abstract : Background: Refractory gout is a serious medical condition, which leads to massive deposition of uric acid crystals in the body resulting in the formation of tophi. A new highly effective treatment modality based on the administration of recombinant PEGylated uricase (pegloticase) allows to approach such patients. Pegloticase cleaves uric acid and leads to a profound drop in serum uric acide levels. How this decrease in uric acid in the body affects the resolution of existing tophi is not yet adequately characterized. Objectives: To investigate the effect of intensive lowering of serum uric acid levels by pegloticase on the resolution of tophi in patients with refractory gout. Methods: Descriptive study in patients with refractory gout receiving pegloticase treatment. Serum uric acid levels were measured before and after each infusion. Dual energy computed tomography scans were taken from all patients before the first infusion and after the last infusion. Computerized tophus volumes were calculated for the baseline and follow up assessments and compared with each other. Results: Ten patients with refractory gout and baseline mean serum uric acid level of 8.1 mg/dL were enrolled. Pegloticase effectively reduced tophi in all patients showing a decrease in volume by 71.4%. Responders, showing reduction of serum uric acid level below 6 mg/dl during at least 80% of the treatment time, were virtually cleared from tophi (-94.8%). Dependent on their anatomical localization, resolution of tophi showed different dynamics, with articular tophi showing fast and tendon tophi slow resolution. Conclusions: Tophi are highly sensitive to pegloticase treatment, particularly when located at articular sites. Debulking of disease and a tophus-free state can be reached within a few months of pegloticase treatment. DECT allows for comprehensively assessing tophus burden and monitoring treatment responses. Disclosure of Interest: None declared